2018
DOI: 10.29137/umagd.419662
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study of the Optical Measurement Sensitivity of the Phototransistor and Photodiode

Abstract: Depending on the amount of light they receive, the light-sensitive circuit elements generate electrical signals such as current, voltage, and resistance. Thus, these sensors are widely used in light measurement systems, light control systems, and opto-couplers. In this study underhand, the electrical values produced by the application of increasing light on the photodiodes and phototransistors are analysed. According to values obtained, the 9.44 standard deviation shows that photodiode has a better performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Meanwhile, sensitivity was taken from each component standard deviation value. This deviation means an electrical response concerning light, where a better variation profile in terms of sensitivity and precision [22]. For the deviation value for each sensor, the authors would like to propose using Wendy's and colleague's research results [23].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, sensitivity was taken from each component standard deviation value. This deviation means an electrical response concerning light, where a better variation profile in terms of sensitivity and precision [22]. For the deviation value for each sensor, the authors would like to propose using Wendy's and colleague's research results [23].…”
Section: Resultsmentioning
confidence: 99%
“…Both current outputs showed linearity, but the RGB color sensor current output has greater linearity and uniformity in response to variable illumination than the phototransistor. The sensitivity of the sensors was taken from the current standard deviation value of each sensor [19]. It is observed that both sensors respond exponentially to light, but while the value of the standard deviation of the RGB color sensor is 20.26, the phototransistor is 30.52.…”
Section: Performance Analysismentioning
confidence: 99%

IoT Based Smart Palm Oil Seed Segregator using RGB Color Sensor

Izzatul Nadia Azhar,
Azlina Idris,
Nugrahini Susantinah Wisnujati
et al. 2024
ARAM
“…In many studies in the literature, there are lux meter circuits created by using LDR [10][11][12][13]. For the calibration of this type of circuits, generally 'real/professional' lux meters are used [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It can communicate with other devices on the same network over the internet browser. When the studies in the literature were examined in detail, it was seen that the resistance of the LDR was read for calibration in many studies and these data were collected manually with multimeters [12,14]. This type of data recording method is limited by the accuracy of the multimeter and is generally performed with low precision.…”
Section: Introductionmentioning
confidence: 99%